EFFECT OF MAGNESIUM TREATMENT PROCESS ON THE PRODUCING COMPACTED GRAPHITE CAST IRON WITH DIFFERENT CASTING THICKNESS - Wiwik Purwadi; Tama Ramadhani; Betti Ses Eka Polonia; Yusuf Yusuf (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2021)
Strength, toughness, machinability and damping capacity are properties of compacted graphite iron that distinguish the properties between flake graphite cast iron and spheroidal cast iron. The formation of compacted graphite can be set to achieve the required specification. The formation of compacted graphite is started from spheroidal to compacted cast iron. The residual magnesium after magnesium treatment and the solidification rate have a significant role in the formation of compacted graphite. The high content of residual magnesium can obstruct the graphite plane to grow during the transformation from spheroidal to compacted shape. In addition, the cooling rate of the casting can be controlled by varying the casting thickness. The compacted graphite in the cast iron are characterized according to shape, size and distribution. The optimum compacted graphite in the cast iron that can be produced has 30 mm of casting thickness with 0.017 % of residual magnesium.